2013
DOI: 10.1094/pdis-09-12-0834-re
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Semiarid Cropping Systems on Root Diseases and Inoculum Density of Soilborne Pathogens

Abstract: Smiley, R. W., Machado, S., Gouriie, J. A., Pritchett, L. C, Yan, G. P, and Jacobsen, E. E. 2013. Infiuence of semiarid cropping systems on root diseases and inoculum density of soilbome pathogens. Plant Dis. 97:547-555.There is interest in converting the 2-year rotation of rainfed winter wheat with cultivated fallow in the Pacific Northwest of the United States into direct-seed (no-till) systems that include chemical fallow, spring cereals, and food-legume and brassica crops. Eight cropping systems in a low-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…It had already been demonstrated that tillage has a strong impact on the soil food web (Hendrix et al, 1986;Zhong et al, 2016) which could affect some of the PPN taxa by modifying the availability of weed roots. Here we highlighted the negative impact on Pratylenchus and Macrotrophurus, in line with the findings of Smiley et al (2013). In contrast with superficial tillage, tillage modifies the soil more deeply (Altieri, 1999;Franzluebbers, 2002), which could have a significant impact on their abundance (Rahman et al, 2007).…”
Section: Effects Of Soil Operationssupporting
confidence: 88%
“…It had already been demonstrated that tillage has a strong impact on the soil food web (Hendrix et al, 1986;Zhong et al, 2016) which could affect some of the PPN taxa by modifying the availability of weed roots. Here we highlighted the negative impact on Pratylenchus and Macrotrophurus, in line with the findings of Smiley et al (2013). In contrast with superficial tillage, tillage modifies the soil more deeply (Altieri, 1999;Franzluebbers, 2002), which could have a significant impact on their abundance (Rahman et al, 2007).…”
Section: Effects Of Soil Operationssupporting
confidence: 88%
“…Black point disease caused by Bipolaris sorokiniana and Alternaria alternata, is an important seed-borne disease in many wheat growing countries of the world ( Zishan et al, 2005;Hasabnis et al, 2006). Smiley et al, (2013) depicted that Fusarium spp. cause crown rot and often invade the emerging coleoptile and also reported that mostly wheat diseases are caused by fungi which attack seed, roots and foliage.…”
Section: Introductionmentioning
confidence: 99%
“…FCR is a chronic disease in most cereal producing regions and its prevalence and severity becomes pronounced under dryland conditions. It is of key economic significance to Australia, costing over A$80 million annually (Murray & Brennan, ), North America (Smiley et al ., ), South Africa (Lamprecht et al ., ) and west Asia and north Africa. FCR is predominantly caused by FP and F. culmorum , but others including F. acuminatum , F. avenaceum , F. crookwellense , F. equiseti and FG may also be involved (Akinsanmi et al ., ; Hogg et al ., ).…”
Section: Introductionmentioning
confidence: 99%